Outcome of structured health education intervention for obesity-risk reduction among junior high school students: Stratified cluster randomized controlled trial (RCT) in South India - Jaun Z Rizvi; Pawan Kumar; Muralidhar M Kulkarni; Asha Kamath (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Obesity has been identified as a serious global health concern whose prevalence doubles almost every 10 years. Health education regarding physical activity and healthy diet imparted to adolescents could prove to be fruitful in reducing obesity-risk. Objectives of this study were to evaluate the effect of health education intervention on knowledge, attitude, and practices (KAP) regarding obesity-risk reduction and to estimate the postinterventional change in body mass index (BMI) and total body fat (%) among adolescent school children in South India. MATERIALS AND METHODS: Stratified cluster randomized controlled trial was carried out among 398 students recruited at baseline including 206 and 192 participants in intervention and control group respectively selected through simple random sampling from eligible government aided and private schools to assess KAP regarding physical activity and diet using pretested and validated questionnaire by making three school visits 6 months apart. Anthropometric measurements were recorded in first and third visit only, while health education intervention was given in first visit to intervention and third visit to control group after taking their responses on the questionnaire. Data were entered and analyzed using SPSS version 15. RESULTS: Overall dropout rate was 13.5% with dropout in intervention and control group being 12.6% and 14.5% respectively, making 180 participants in intervention and 164 in control group available for analysis. Mean physical activity KAP score improved significantly from 16.19 ± 4.61 to 19.46 ± 10.07 in intervention group. Mean dietary KAP score also improved significantly from 21.38 ± 4.07 to 23.43 ± 4.53 in intervention group (p < 0.001). Mean BMI decreased significantly within intervention group (p < 0.001) as compared to control group (p = 0.908). Based on cut-off level for total body fat (%) to categorize obesity-risk among participants, statistically significant decline in proportions from 26.1% to 13.3% was observed in intervention group (p < 0.001). CONCLUSION: Results depicted better KAP in intervention group than control group in all the three visits while it improved significantly within both groups. Hence, the health education was found to be effective in improving the overall KAP regarding modifiable risk factors of obesity among the study participants. Further studies to screen the adolescents for obesity-risk and successive health education sessions must be carried within schools in order to bring about change in knowledge, attitude, and practices regarding obesity-risk.